2002
DOI: 10.1128/iai.70.7.3493-3499.2002
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Protective Immunity to Malaria Induced by DNA Priming and Poxvirus Boosting: Characterization of Effector and Memory CD8+-T-Cell Populations

Abstract: The persistence of immunity to malaria induced in mice by a heterologous DNA priming and poxvirus boosting regimen was characterized. Mice were immunized by priming with DNA vaccine plasmids encoding the Plasmodium yoelii circumsporozoite protein (PyCSP) and murine granulocyte-macrophage colony-stimulating factor and boosting with recombinant vaccinia encoding PyCSP. BALB/c mice immunized with either high-dose (100 g of p PyCSP plus 30 g of pGM-CSF) or low-dose (1 g of p PyCSP plus 1 g of pGM-CSF DNA) priming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…In the DNA-MVA prime-boost regimen in mice, protective efficacy against P. berghei fell from 100% at 14 days post MVA to 60% at day 150 (J. Schneider, personal communication). Durability of protection was characterised in more detail for prime-boost regimens in the P. yoelii model, with a drop in efficacy from 70-100% at 20 weeks to 30-40% at 28 weeks (Sedegah et al, 2002).…”
Section: Murine Studiesmentioning
confidence: 99%
“…In the DNA-MVA prime-boost regimen in mice, protective efficacy against P. berghei fell from 100% at 14 days post MVA to 60% at day 150 (J. Schneider, personal communication). Durability of protection was characterised in more detail for prime-boost regimens in the P. yoelii model, with a drop in efficacy from 70-100% at 20 weeks to 30-40% at 28 weeks (Sedegah et al, 2002).…”
Section: Murine Studiesmentioning
confidence: 99%
“…We therefore used the Plasmodium yoelii murine malaria model to study the efficacy of immunizing (priming) 7-day-old neonatal mice with a DNA plasmid expressing the P. yoelii circumsporozoite protein (PyCSP) 3 and boosting them at the age of 28 days with a recombinant poxvirus expressing the PyCSP. This specific regimen was chosen for study in neonatal mice, because our extensive previous studies (4,6,14) have demonstrated it to be much more effective than any other regimen we have assessed in eliciting the CD8 T cell responses, we and others consider it to be critical for protective immunity against the liver stages of Plasmodium sp. parasites (15,16).…”
Section: Successful Induction Of Cd8 T Cell-dependent Protectionmentioning
confidence: 99%
“…Protective CD8 T cell immunity against liver-stage Plasmodium infection has been demonstrated after vaccination of rodents with irradiated or genetically attenuated parasites and after subunit vaccination against liver-stage antigens (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Immunity in rodents can last for 6-12 months (3,4,7,13), but in several studies also seems to wane with time (7,(14)(15)(16).…”
mentioning
confidence: 99%